A Comparative Study of Diastolic Dysfunction by Echocardiography among Diabetic and Non-Diabetic Subjects - Virendra C. Patil; Harsha V. Patil; Aniket B. Avhad; Akshay R. Kulkarni (Journal of Krishna Institute of Medical Sciences University, 2020)
Background: Cardiovascular Disease (CVD) is the most significant prognostic factor in individuals with Type 2 Diabetes (T2D). The myocardial damage in diabetic subjects affects diastolic function before the systolic function. Aim and Objectives: To compare the diastolic dysfunction and its parameters (E/A ratio, E/e' ratio) by transthoracic echocardiography among diabetic and non-diabetic patient and to find relation between diastolic dysfunction and HbA1c. Material and Methods: This was a prospective, observational and case control study. Diabetes Mellitus (DM) was labeled if Fasting Blood Sugar (FBS) ≥ 126 mg/dL or HbA1c ≥ 6.5%. Standardized Transthoracic Echocardiographic (TTE) examination was performed (American Society of Echocardiography). Left Ventricular Diastolic Dysfunction (LVDD) was labeled if 3 or more of these variables are abnormal: "Septal e <7 cm/sec, Lateral e <10 cm/sec), E/e ratio >14, LA volume index 2 >34 mL/m , Peak TR velocity >2.8 m/sec." Results: A total of 50 subjects with Type 2 Diabetes Mellitus (T2DM) cases and 50 healthy age and gender matched controls were included in this study. The peak early trans-mitral filling wave velocity (E) in diabetic population was low in diabetes subjects [41 ± 12 cm/s vs 48 ± 8.5 cm/s]. Mean of E/A ratio in the Study Group was significantly lower as compared to the Control Group ('p' = 0.02). The E/e' ratio was significantly higher in diabetic group (16.5 ± 2.7 vs 14.13 ± 1.92) compared to Control Group. T2DM group had lower E/Aratio, deceleration time, e' compared to the controls and higher E/e' ('p' < 0.02). Total 21 (42%) subjects among diabetes mellitus had diastolic dysfunction [Grade I: 19 (38%) and Grade-II: 2 (4%)]. Total 2 (4%) subjects among control had diastolic dysfunction [Grade I: 2(4%)] ('p' < 0.00001). Age, Body Mass Index (BMI), Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Left Ventricular Ejection Fraction (LVEF), duration of DM and HbA1c had negative correlation with parameters of diastolic dysfunction [E (cm/s),E/A, e', E'sr] and positive correlation with A, TR jet, Left Atrial Volume index (LAVi) and E/E'sr ratio. Conclusion: Present study highlighted the burden of diastolic dysfunction (42%) among the asymptomatic diabetic subjects with predominance of Grade I diastolic dysfunction. Age, BMI, blood pressure, duration of DM, HbA1c had negative correlation with parameters of diastolic dysfunction [E (cm/s),E/A, e', E'sr] and positive correlation with TR jet, LAVi, E/E'sr ratio.